Genomic inbreeding and runs of homozygosity analysis of indigenous cattle populations in southern China. - Yuqiang Liu; Guoyao Zhao; Xiaojue Lin; Jiahao Zhang; Guanyu Hou; Luepei Zhang; Dewu Liu; Yaokun Li; Junya Li; Lingyang Xu (PLoS ONE, 2022)
Runs of homozygosity (ROH) are continuous homozygous segments from the common ancestor of parents. Evaluating ROH pattern can help to understand inbreeding level and genetic basis of important traits. In this study, three representative cattle populations including Leiqiong cattle (LQC), Lufeng cattle (LFC) and Hainan cattle (HNC) were genotyped using the Illumina BovineHD SNPs array (770K) to assess ROH pattern at genome wide level. Totally, we identified 26,537 ROH with an average of 153 ROH per individual. The sizes of ROH ranged from 0.5 to 53.26Mb, and the average length was 1.03Mb. The average of FROH ranged from 0.10 (LQC) to 0.15 (HNC). Moreover, we identified 34 ROH islands (with frequency > 0.5) across genome. Based on these regions, we observed several breed-specific candidate genes related to adaptive traits. Several common genes related to immunity (TMEM173, MZB1 and SIL1), and heat stress (DNAJC18) were identified in all three populations. Three genes related to immunity (UGP2), development (PURA) and reproduction (VPS54) were detected in both HNC and LQC. Notably, we identified several breed-specific genes related to sperm development (BRDT and SPAG6) and heat stress (TAF7) in HNC, and immunity (CDC23 and NME5) and development (WNT87) in LFC. Our findings provided valuable insights into understanding the genomic homozygosity pattern and promoting the conservation of genetic resources of Chinese indigenous cattle.